2018
DOI: 10.4149/neo_2018_171218n824
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of MEOX2 promotes apoptosis through inhibiting the PI3K/Akt pathway in laryngeal cancer cells

Abstract: The early-stage diagnosis and treatment for the recurrence of larynx carcinoma needs further investigation. Mesenchyme homeobox 2 (MEOX2) was speculated as a novel suppressor gene in larynx carcinoma in our study, the molecular mechanism was studied. Real-time quantitative PCR (RT-qPCR) and Western blot were used to detect mRNA and protein levels of MEOX2 in laryngeal cancer tissues and cells (Hep-2, TU212, AMC-NH-8 and TU686 cells), and also apoptosis and phosphoinositide 3-kinase (PI3K)/protein kinase (Akt) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…As reported previously, Meox2 is involved in regulation of the PI3K/AKT signaling pathway (Liu et al, 2015;Tian et al, 2018).…”
Section: Mir-148a-3p Affects the Pi3k/akt Signaling Pathway In Smscssupporting
confidence: 62%
“…As reported previously, Meox2 is involved in regulation of the PI3K/AKT signaling pathway (Liu et al, 2015;Tian et al, 2018).…”
Section: Mir-148a-3p Affects the Pi3k/akt Signaling Pathway In Smscssupporting
confidence: 62%
“…For example, single-nucleotide polymorphism-based sequencing studies reported that MEOX2 served as a tumor suppressor gene in Wilms' tumor (25). In another study, MEOX2 expression was upregulated in laryngeal carcinoma and lung cancer tissues (26,27), and the overexpression of MEOX2 promoted laryngeal cancer growth by activating the PI3K/AKT signaling pathway. The upregulated expression levels of MEOX2 were also found to contribute to chemoresistance in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Not only is hyperactivation of PI3K/AKT pathway in relation to NPC progression and prognosis [79], but FOXO1, CHL1, PNUTS, VPS33B interacts with NESG1, RBM3, ARHGAP42 and LncRNA ZFAS1 also display their influence on the proliferation, growth, invasion, metastasis, EMT, chemosensitivity or radio-resistance of NPC cells via PI3K/AKT pathway [93]. Additionally, MMP2/3, MEOX2, miR-145 and -138 regulate the growth, apoptosis or migration of LSCC cells by targeting the PI3K/AKT pathway [94][95][96][97].…”
Section: Characterization Of the Pi3k/akt Pathway In The Respiratory mentioning
confidence: 99%